Menimbang Gagasan Bryan S. Turner tentang Islam - Imam Turmudi (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article explores the study of Islam by an orientalist, Bryan S. Turner. This study aimed to first uncover the things that underlie the history of thought and movement of Orientalism. Second, to determine Bryan S. Turner's thought about Islam, which is specifically intended as a corrective to the thesis produced by Max Weber about his interpretation of Islam. The study results reveal that historically Orientalism or the oriental studies movement emerged in the 18th century. This movement is often associated as a movement that pretends to control and weaken the East, especially Islam. It is not without basis, since the emergence of Orientalism has led to intellectual arrogance by claiming the West as a measure of civilization because the East presented only in accordance with the construction used by the West.